Robot modeling and control - Spong, Mark W.; Hutchinson, Seth.; Vidyasagar, M. (Mathukumalli), 1947- (Hoboken, NJ : John Wiley and Sons, 2006)
{09}Introduction -- Rigid motions and homogeneous transformations -- Forward and inverse kinematics -- Velocity kinematics-The Jacobian -- Path and trajectory planning -- Dynamics -- Independent joint control -- Multivariable control -- Force control -- Geometric non-linear control -- Computer vision -- Vision-based control -- Appendix A Trigonometry -- Appendix B Linear algebra -- Appendix C Dynamical systems -- Appendix D Lyapunov stability -- Index.
Includes bibliographical references (pages 459-470) and index.
Keywords: Robots -- Control systems; Robotics